Axial Spondyloarthritis Treatment Recommendations in 2024: Where Are We Now? (Canadian Rheumatology Today, 2024)
As 2024 continues to evolve, so do treatment recommendations for the management of spondyloarthritis (SpA), including ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA). From a Canadian perspective, we eagerly await the publication of the Canadian Rheumatology Association (CRA)/Spondyloarthritis Research Consortium of Canada (SPARCC) Living Treatment Recommendations for the Management of Axial Spondyloarthritis (axSpA), currently in press. Until these recommendations for axSpA treatment with a Canadian perspective arrive  – where are we now?